MENCARI FORMAT BARU PENDIDIKAN BERBASIS MULTIKULTURAL DI INDONESIA - Tanto Sukardi; Subandowo subandowo (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2014)
This article aims to fi nd a new format of education based multicultural reality in Indonesia. For that purpose, the authors conducted a literature study, especially those related to the concepts of multicul tural education for the development of education in Indonesia. As it is known that the current Indonesian society is still in the process of forming a national culture. This is not an easy task, because of the heterogeneous ethnic cultures that have each own character. When the formation of a national culture has not been successful, the peopl e of Indonesia also have to deal with the increasingly intense global culture. Pressures of today’s global culture is sometimes met with reactionary and primordial attitude. As evidence, the emergence of a kind of spiritual religious movement radicalism and fundamentalism form of Sufi sm on youth. Meanwhile, the traditional sentiment which is basically a consequence of the structural changes and cultural changes inkosisten, resulting in the emergence of symptoms of chaos in the system of local cultural values that exist. These conditions are necessary to fi nd a way out so that the process of interaction between local cultures remain in harmony with the national cu lture. Format suitable for the purpose as it is through multicultural education.